2022
DOI: 10.3390/clockssleep4040051
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Blue-Light-Emitting Glasses in Security Guards Exposed to Night Shift Work on Work-Related and General Fatigue: A Randomised Controlled Cross-Over Study

Abstract: This study aimed to evaluate the effectiveness of glasses that emit blue light in reducing the need for recovery, general fatigue, and stress levels in security guards who work night shifts. Light manipulation is seen as a promising strategy to mitigate complaints related to shift work, such as sleepiness and impaired cognitive performance. In a randomized controlled cross-over study design, 86 Dutch security guards used light-emitting glasses (exposure duration: 30 min) during night shifts in a five week peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Previous studies have reported the potential of a brighter environment on reducing sleepiness in ICU nurses and security guards [ 4 , 5 ]. However, the effect we observed was very limited.…”
mentioning
confidence: 99%
“…Previous studies have reported the potential of a brighter environment on reducing sleepiness in ICU nurses and security guards [ 4 , 5 ]. However, the effect we observed was very limited.…”
mentioning
confidence: 99%